The Correlation Between Project Learning Models and Student Activities in Online Learning for Chemistry Innovative Learning Model - Oktaffi Arinna Manasikana; Nindha Ayu Berlianti; Nur Hayati (Journal of Educational Chemistry (JEC), 2023)
This study aims to determine the effectiveness of project learning on student activity in chemistry innovative learning models courses. The research conducted used the experimental method. The results showed that students’ activeness in action was included in the successful category, which is 72.7%, and student activity in understanding the innovative learning model was included in the successful category, which is 63.6%. Student responses to project learning are included in the very successful category at 81.8%. The results of statistical research using partial regression correlation analysis techniques and multiple correlations show a significant positive relationship between project learning and learning effectiveness with a correlation coefficient (ry1) = 0.201. A significant positive relationship exists between student activities in innovative chemistry learning models and learning effectiveness with a correlation coefficient (ry2) = 0.759. There is a significant positive relationship between project learning and student activities and learning effectiveness with a correlation coefficient (ry12) = 0.769. Based on the results of these studies, it can be concluded that the effectiveness of learning can be increased through project learning and student activities.